The use of heat-assisted antigravity drainage method in the two horizontal wells in gas production from the Qilian Mountain permafrost hydrate deposits - Li, Bo; Li, Gang; Li, Xiao-Sen; Chen, Zhao-Yang; Zhang, Yu (Journal of Petroleum Science and Engineering, 2014)
The occurrence of gas hydrate deposits in the Qinghai-Tibet plateau permafrost (QTPP) were confirmed during the Scientific Drilling Project of Gas Hydrate in Qilian Mountain permafrost (QMP) in 2008-2009. A total of four test wells were completed, and gas hydrate samples were obtained from the drilling wells of DK-1, DK-2, and DK-3. The objective of this study is the analysis of gas production potential from gas hydrate-bearing zone of DK-2 using dual horizontal wells based on its geological properties at this site. In this paper, production strategies of permafrost hydrate deposits with the novel Heat-Assisted Antigravity Drainage (HAAD) method are investigated numerically. Gas production is induced in a two-well system and its influence factors are evaluated. When suitable heat injection rate and depressurization driving force are applied to the lower well and the upper well, respectively, favorable gas-to-water ratio and energy ratio can be obtained during the whole HAAD process. However, the absolute gas production rate may not be economically attractive for the production method we have employed. The sensitivity analysis indicates that the hydrate deposits with higher intrinsic permeability and larger rock porosity will show better perspective for hydrate exploitation. (C) 2014 Elsevier B.V. All rights reserved.